2019
DOI: 10.1080/1343943x.2019.1617638
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for improving N use efficiency for rice production in sub-Saharan Africa

Abstract: In sub-Saharan Africa (SSA), rice production from smallholder farms is challenged because of a lack of fertilizer inputs and nutrient-poor soils. Therefore, improving nutrient efficiency is particularly important for increasing both fertilizer use and rice yield. This review discusses how to improve the return from fertilizer input in terms of agronomic N use efficiency (AE N), that is, the increase in grain yield per kg of applied N, for rice production in SSA. The AE N values we summarized here revealed larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 92 publications
6
67
0
Order By: Relevance
“…However, world resources of P are finite and thus, P should be used as efficiently as possible in order to conserve the base resources [4]. Efficient P fertilizer management is also key to improving rice yield for smallholder farmers who use few external inputs, such as in the case of Sub-Saharan Africa [5]. Therefore, it is necessary to find appropriate strategies for the effective use of P fertilizers in rice production systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, world resources of P are finite and thus, P should be used as efficiently as possible in order to conserve the base resources [4]. Efficient P fertilizer management is also key to improving rice yield for smallholder farmers who use few external inputs, such as in the case of Sub-Saharan Africa [5]. Therefore, it is necessary to find appropriate strategies for the effective use of P fertilizers in rice production systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, rice yields in SSA have remained low because of several biotic and abiotic stresses. Among these various stresses, P deficiency is a major constraint for rice production in highly weathered soils in SSA (Dogbe et al, 2015;Saito et al, 2019). P deficiency to rice is commonly observed in Madagascar, the second largest rice producer in SSA, which is due to high levels of P-fixing iron (Fe) or aluminum (Al) oxyhydroxides in soils (Nishigaki et al, 2019) and little P fertilizer inputs (Rabeharisoa et al, 2012;Tsujimoto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among these various stresses, P deficiency is a major constraint for rice production in highly weathered soils in SSA (Dogbe et al, 2015;Saito et al, 2019). P deficiency to rice is commonly observed in Madagascar, the second largest rice producer in SSA, which is due to high levels of P-fixing iron (Fe) or aluminum (Al) oxyhydroxides in soils (Nishigaki et al, 2019) and little P fertilizer inputs (Rabeharisoa et al, 2012;Tsujimoto et al, 2019). Our previous on-farm experiments demonstrated that the yield gap between P-fertilized and non-P-fertilized treatments could reach up to 2.5 t ha -1 in the central highlands of Madagascar (Andriamananjara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the local paddy rice varieties grown in wetlands are late maturing (120 -140 days), and susceptible to diseases, indicating a need to adopt and adapt the improved varieties to the prevailing farming conditions. Moreover, decline in soil fertility has also caused an increase in the cost of production [7], and overuse of fertilizers that may eventually have a negative impact on the entire wetland ecosystem. Therefore, enhancing the ability of rice plants to tolerate biotic and abiotic stresses is the current strategy for increasing agricultural productivity worldwide.…”
Section: Introductionmentioning
confidence: 99%